2017
DOI: 10.1111/cdev.13009
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Security Priming Decreases Children's Physiological Response to Threat

Abstract: Ninety 6- and 7-year-olds (49.3% White, mostly middle class) from greater Washington, DC were randomly assigned to a subliminal priming condition (secure, happy, or neutral) to determine if attachment security priming decreases physiological, expressive, and self-reported fear reactions to threatening stimuli. Dispositional attachment security was also assessed. Secure priming and attachment security each decreased electrodermal reactivity, increased vagal augmentation, and decreased fearful facial expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Across studies 3459 participants received priming. The samples largely consisted of university students, but two tested child and adolescent participants [24], [26] (b), one a clinical sample [27], and one heterosexual romantic couples [29] (c). Most studies reported age ranges between 6 to 76 year, mean-21.9 years but not all [25], [29] (a-c), [30].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Across studies 3459 participants received priming. The samples largely consisted of university students, but two tested child and adolescent participants [24], [26] (b), one a clinical sample [27], and one heterosexual romantic couples [29] (c). Most studies reported age ranges between 6 to 76 year, mean-21.9 years but not all [25], [29] (a-c), [30].…”
Section: Methodsmentioning
confidence: 99%
“…Most studies reported age ranges between 6 to 76 year, mean-21.9 years but not all [25], [29] (a-c), [30]. Studies were conducted in five countries: twelve in Israel [17] (a-e), [33] (a-g), ten in the US [24], [26] (a,b), [29] (a-c), [30,31], [32] (b), six in the UK [13,18], [22] (a,b), [25,27], one in China [16] and one in Canada [32] (a). The average percentage of females across studies was 64.3%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations